Solar fed BLDC motor drive for mixer grinder using a buck-boost converter - Deekshitha S. Nayak; R. Shivarudraswamy (Institute of Advanced Engineering and Science, 2020)
In existing mixer grinders, the universal motor is used due to its high starting torque than the induction motor. To achieve higher speed for smaller devices, the implementation of the universal motor becomes cheaper. The absence of brushes and the reduction of noise in the BLDC extends its lifetime, making it ideal for a mixer grinder. The solar-powered BLDC motor drive for a mixer grinder is presented in this paper. A DC-DC buck boost (BB) converter is utilised to operate the PV (photovoltaic) array at its highest power. The proposed hysteresis current (HC) control BLDC system is developed in the MATLAB. A comparison performance is demonstrated between the commercially available mixer grinder and the simulated proposed system.